Implementation Model Learning Innovation of direct Learning in Social Sciences at Elementary School - Elfa , (Prosiding Seminar Nasional Jurusan PGSD FIP UNP Tahun 2015, 2015)
The background of this research in an elementary school, a teacher lacking conveying learning objectives, lack of providing skills to students, lack of training, and lack of feedback to the student in the learning process social sciences. This problem affects the students are less active and creative, so the study results is below the average KKM (6) specified in the school. This study aimed to describe